ETHICAL RESPONSIBILITY AS A RESOLUTION TO ANXIETY. A PSYCHOANALYTICAL PERSPECTIVE ON THE FACE OF THE OTHER - DIOȘAN, Livia (Studia Universitatis Babeș-Bolyai Philosophia, 2018)
Our perspective aims to fathom to what extent Emmanual Lévinas’s philosophical and Talmudic texts deliver a manner of assuming anxiety or a resolution of anxiety. To achieve this, we propose the Lacanian concept of the Name of the Father, and we use a reading of the Lévinasian corpus aided by the theoretical developments offered by mainly Freudian and Lacanian psychoanalysis. We analyze the relation to the Face as a condition for the occurrence of the Other in his transcendence, from his height, as well as the interdiction against killing. The Face is simultaneously gaze and voice. We analyze the Lévinasian responsibility in relation to the Face as a resolution in the symbolic order of the radical anxiety in front of the Face of A-Elohim, in a face-to-face relation which could be a face-to-face relation with the text of the Torah that is the written trace of Infinity.